TELAAH TEORETIS MODEL EXPERIENTIAL LEARNING DALAM PELATIHAN KEWIRAUSAHAAN PROGRAM PENDIDIKAN NON FORMAL - Prasetya, Iis (MAJALAH ILMIAH PEMBELAJARAN, 2011)
This paper aims to examine the model of experiential learning,theoretically, and to consider it's appropriateness to be applied inentrepreneurship training, especially in non-formal educationprograms.The Characteristics contained in this learning model is in accordancewith the characteristics of the learner of non-formal educationprograms. Thus, philosophically speaking, learning experiential modelis in accordance with the philosophy of non-formal education.Therefore, this accordance create the possibility of this modelapplication in non-formal education programs, specifically those whichaimed at improving or developing the entrepreneurial spirit and learnerin the community.